Source material for naked barley breeding in the Northwest of the Russian Federation - K. A. Lukina; I. G. Loskutov; V. I. Khoreva; O. N. Kovaleva (Труды по прикладной ботанике, генетике и селекции, 2025)
Background. Barley (Hordeum vulgare L.) is the earliest in maturity and most flexible cereal crop, with a wide variety of forms. There are the groups of covered and naked varieties within the cultivated barley species. The interest in naked barley has currently re-emerged due to easy separation of floral glumes from the kernel during threshing and increased content of biochemical components. However, breeders in Russia are still paying much less attention to naked barleys that they do to covered ones.Materials and methods. In 2021–2023, 271 naked barley accessions from the VIR collection were studied in the experimental field of Pushkin and Pavlovsk Laboratories of VIR. The set included two-row (115 accessions) and six-row (156 accessions) barleys of various ecogeographic origin. Their growing season duration, yield, and protein content were analyzed.Results. Field and laboratory studies resulted in making agrobiological descriptions of the accessions and identifying sources of individual agronomic traits (earliness, high yield, and good grain quality) and their combinations under the conditions of the Russian Northwest. The diversity of naked barleys of various origin was shown for all the studied traits.Conclusion. Twelve ultra-early and 53 early naked barley accessions were selected as potential sources of earliness for breeders. Ten two-row and 10 six-row accessions were identified as high-yielding, while 8 two-row and 15 six-row accessions had the highest protein content (above 20%). Correlations among the studied traits were specified for the studied set of naked barleys. The selected source material will be offered to the leading breeding centers of Russia for the development of new cultivars with desired traits.